2011
DOI: 10.1186/1745-6215-12-122
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of reporting of randomization, allocation concealment, and blinding in traditional chinese medicine RCTs: A review of 3159 RCTs identified from 260 systematic reviews

Abstract: BackgroundRandomized controlled trials (RCTs) which are of poor quality tend to exaggerate the effect estimate and lead to wrong or misleading conclusions. The aim of this study is to assess the quality of randomization methods, allocation concealment and blinding within traditional Chinese medicine (TCM) RCTs, discuss issues identified for current TCM RCTs, and provide suggestions for quality improvement.MethodsWe searched Chinese Biomedical Database (CBM, 1978 to July 31, 2009) and the Cochrane Library (Issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 28 publications
2
44
1
Order By: Relevance
“…Although the quality of reporting RCTs of TCMs has been enhanced in the past decade, more and more academics realize that the percentage of high quality reports remains low, exacerbating the ROB problem relevant to TCMs trials [3941]. Researchers should take responsibility for making registration of clinical trials [42], paying more attention to experiment design and methodological quality [43], and receiving education to write high quality report, so as to increase the credibility of TCMs studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the quality of reporting RCTs of TCMs has been enhanced in the past decade, more and more academics realize that the percentage of high quality reports remains low, exacerbating the ROB problem relevant to TCMs trials [3941]. Researchers should take responsibility for making registration of clinical trials [42], paying more attention to experiment design and methodological quality [43], and receiving education to write high quality report, so as to increase the credibility of TCMs studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, information on the method of random sequence generation, primary outcome, sample size calculation, randomization stated in title, allocation concealment, and adequate blinding was reported in 34, 53, 45, 33, 25, and 18% of 616 reports indexed in PubMed in 2006, respectively [84]. Especially, in RCTs of traditional Chinese medicine that include herbal medicine, acupuncture and other no medication therapies, reporting of the key methods used for adequate randomization methods, adequate allocation concealment, adequate blinding, both adequate randomization methods and allocation concealment used, and all three used was only 12, 7, 19, 4, and 3% of 2580 reports, respectively [8]. Thus, several guidelines have been recommended to help incomplete and inaccurate reporting.…”
Section: Discussionmentioning
confidence: 99%
“…However, a large body of evidence indicated that the quality of reporting of RCTs remains sub-optimal [7]. Researchers have accumulated and suggested that the RCTs which were of poor methodological quality tend to exaggerate the treatment effects and result in misleading in health care at all levels [8]. So far, two studies have already been conducted to evaluate the quality of reporting of RCTs on acupuncture for stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Hewitt et al (55) reported that more than 40% of trials published in 2004 in Western medical journals either failed to use adequate randomization methods or failed to report the method for concealment of allocation. Furthermore, He et al (56) reported that the methodological quality of 579 RCTs published in 2009 in foreign journals was generally poor, 75% failed to use adequate randomization methods, and 74% failed to report adequate allocation concealment.…”
Section: Discussionmentioning
confidence: 98%